2019
DOI: 10.1186/s13550-019-0585-7
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the aggressiveness of non-functional pancreatic neuroendocrine tumors based on the dual-tracer PET/CT

Abstract: Background: Predicting the aggressive behavior of non-functional pancreatic neuroendocrine tumors (NF-PNET) remains controversial. We wanted to explore, in a prospective setting, whether the diagnostic accuracy can be improved by dual-tracer functional imaging 68 Ga-DOTANOC and 18 F-FDG-PET/CT in patients with NF-PNETs. Methods: Thirty-one patients with NF-PNET (90% asymptomatic) underwent PET-imaging with 18 F-FDG and 68 Ga-DOTANOC, followed by surgery (n = 20), an endoscopic ultrasonography and fine-needle b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…Other types of positron emission tomography (PET) 18 FDG-PET and SRI provide complementary information regarding the different biological characteristics of the lesions. Prognosis is generally worse if a tumour is 18 FDG positive and SRI negative and vice versa [17][18][19]. 18 FDG-PET should be performed in localised NET G3 as well as in NECs and may be valuable in G1-2 NETs for prognostication and therapy planning.…”
Section: Somatostatin Receptor Imaging (Sri)mentioning
confidence: 99%
“…Other types of positron emission tomography (PET) 18 FDG-PET and SRI provide complementary information regarding the different biological characteristics of the lesions. Prognosis is generally worse if a tumour is 18 FDG positive and SRI negative and vice versa [17][18][19]. 18 FDG-PET should be performed in localised NET G3 as well as in NECs and may be valuable in G1-2 NETs for prognostication and therapy planning.…”
Section: Somatostatin Receptor Imaging (Sri)mentioning
confidence: 99%
“…However, only the study by Ilhan et al [ 39 ] specifically addressed this point in a study cohort of pNET patients, in which imaging results altered the surgical management in 6/18 cases (33%), while the remaining studies contained mixed NET patients′ cohorts. In contrast, fewer studies explored the prognostic relevance of SSR-targeted imaging at staging in pNETs [ 20 , 52 ]. Majala et al [ 52 ] showed that 68Ga-DOTANOC integrated with 18F-Fluorodeoxyglucose (FDG) PET/CT can predict tumor grade and clinical outcome in non-functioning pNETs.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, fewer studies explored the prognostic relevance of SSR-targeted imaging at staging in pNETs [ 20 , 52 ]. Majala et al [ 52 ] showed that 68Ga-DOTANOC integrated with 18F-Fluorodeoxyglucose (FDG) PET/CT can predict tumor grade and clinical outcome in non-functioning pNETs. The authors showed that not only FDG but also 68Ga-SSR imaging has prognostic value in the preoperative setting, being able to predict the histopathological grade.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of lymph node metastasis that was identified in our study was 38.7%, which is in line with previously published data by Hashim and colleagues, who reported a rate of 37.6% [ 5 ]. Moreover, a 33.3% rate of lymph node metastasis was reported by the PET/CT screening imaging [ 21 ]. However, our rate of 38.7% may be an overestimation of the true incidence of lymph node metastasis due to the exclusion of low-risk patients that did not undergo nodal sampling due to a low degree of suspicion.…”
Section: Discussionmentioning
confidence: 99%